Photocatalytic characteristics of single phase Fe-doped anatase TiO2 nanoparticles sensitized with vitamin B12. (January 2015) - Gharagozlou, Mehrnaz; Bayati, R.
Graphical abstract: Highlights: Anatase TiO2 /B12 hybrid nanostructured catalyst was successfully synthesized by sol–gel technique. The nanoparticle catalyst was doped with iron at several concentrations. Nanoparticles were characterized in detail by XRD, Raman, TEM, EDS, and spectroscopy techniques. The formation mechanism and role of point defects on photocatalytic properties were discussed. A structure-property-processing correlation was established. Abstract: We report a processing-structure-property correlation in B12 -anatase titania hybrid catalysts doped with several concentrations of iron. Our results clearly show that low-level iron doping alters structure, defect content, and photocatalytic characteristics of TiO2 . XRD and Raman studies revealed formation of a single-phase anatase TiO2 where no iron based segregation in particular iron oxide, was detected. FT-IR spectra clearly confirmed sensitization of TiO2 nanoparticles with vitamin B12 . TEM micrographs and diffraction patterns confirmed crystallization of anatase nanoparticles with a radius of 15–20 nm. Both XRD and Raman signals showed a peak shift and a peak broadening which are surmised to originate from creation of point defects, namely oxygen vacancy and titanium interstitial. The doped samples revealed a narrower band gap as compared to undoped samples. Photocatalytic activity of the samples was assessed through measuring the decomposition rate of rhodamine B. It was found that sensitization with vitamin B12 and Fe-doping significantly enhances the photocatalytic efficiency of the anatase nanoparticles. We also showed that there is an optimum Fe-doping level where the maximum photocatalytic activity is achieved. The boost of photocatalytic activity was qualitatively understood to originate from a more effective use of the light photons, formation of point defects, which enhance the charge separation, higher carrier mobility.